Processamento do licor sulfúrico de terras raras para obtenção dos respectivos concentrados e separação do cério por oxidação térmica - Ruberlan Gomes da Silva (2019)
The aims of this work were to understand the thermal oxidation of Ce3+ to Ce4+ presented in the composition of mixed rare earth oxalates or carbonates. For this, it was carried out analyses of X-ray diffractions and HCl leaching of the mixed rare earth oxides obtained by calcination of the respective mixed rare earth oxalates or carbonates in a muffle in different conditions. In this work, it was used a sample of rare earth ore collected in a phosphate mine located in Brazil. A non-purified rare earth liquor was generated by application of pyro-hydrometallurgical process route to extract selectively the REEs (Rare Earth Elements) from the rare earth ore. The chemical analyses of non-purified rare earth liquor presented the following concentrations: 3.74 gL-1 of REE3+, 2.91 gL-1 of Fe3+, 1.61 gL-1 of PO43-, 8.74 mgL-1 of Th4+, 0.42 gL-1 of Al3+, 3.41 mgL-1 of UO22+, 16.9 gL-1 of SO42-, 0,89 gL-1 of Ca2+, 0.94 gL-1 of Mn2+ and 0.41 gL-1 of Mg2+. The most efficient procedure to purify the rare earth liquor was in two consecutives steps by rising the pH, first by addition of limestone pulp 10% m/m up to a pH of 3.50, following by a filtration to remove the solid residue, and second by addition of lime pulp 10% m/m to the filtrate up to a pH of 5.00, with another filtration to remove the second solid residue. Following this procedure, the REOs (Rare Earth Oxides) losses were only of 4.0% m/m, all Fe3+, PO43- and Th4+ ions were removed and there was reduction of 99%, 87% and 37% in the Al3+, UO22+ and SO42- concentrations, respectively. The chemical analyses of purified rare earth liquor presented the following concentrations: 3.39 gL-1 of REE3+, 4.55 mgL-1 of Al3+, 0.44 mgL-1 of UO22+, 10.5 gL-1 of SO42-, 1.04 gL-1 of Ca2+, 0.94 gL-1 of Mn2+ and 0.46 gL-1 of Mg2+. This liquor was used to generate the mixed rare earth oxalates, carbonates and hydroxides. The mixed rare earth oxides, obtained by calcination in a muffle of the mixed rare earth oxalates at 1100ºC, contained a REOs content of 99.1% w/w (high purity) and with the lowest impurities content. The best condition was the stoichiometric dosage of oxalic acid and temperature of 60ºC. The mixed rare earth carbonates presented a purity of 94.0% and a REOs content of 68.8% w/w. In the same way, the best condition was with the stoichiometric dosage of sodium carbonate and temperature of 60ºC. The mixed rare earth hydroxides presented a purity of 99.7% and a REOs content of 76.6% w/w, being precipitated at 20ºC and adding 10% above the stoichiometric dosage of NaOH. Like what was checked in the literature, it was possible to fix 94% of cerium presented in the composition of mixed rare earth hydroxides by drying at 160ºC per 4 hours in a muffle with air circulation. The dried mixed rare earth hydroxides were leached with HCl solution 2 molL-1 at room temperature (20ºC) and it was generated a cerium concentrate (CeO2.1.2H2O) with REOs content of 76.6%, containing 31% w/w of others rare earth elements and only 0.27% w/w of sulfate. The complete calcination of mixed rare earth oxalates and mixed rare earth carbonates were achieved at temperature do 1100ºC in a muffle. The x-ray diffraction of the product from the calcination of mixed rare earth oxalates at 1100°C showed that it was a mixture of Ce2O3 and CeO2, represented by Ce4O7. On the other hand, it was formed an intermediate crystalline structure between Ce4O7 and CeO2 in the oxides obtained by calcination of mixed rare earth carbonates calcined in the muffle at 1100ºC, which one was identified as Ce0,60Nd0,40O1,80 (Ce1-xNdxO2-x/2, with x=0,40). The Ce4O7 was completely dissolved by a solution of HCl 37% w/w (12 molL-1), temperature of 90ºC and 2 hours stirring, whereas the Ce0,60Nd0,40O1,80 was not solubilized in the same hydrochloric acid leaching condition. The chemical analyses and the x-ray diffractions of the cerium oxides, obtained by calcination in a muffle of pure cerium oxalate and pure cerium carbonate at 1100ºC, showed the formation of the crystalline structures identified as CeO2. Like it was expected, the CeO2 was not dissolved in the same hydrochloric acid leaching condition.